CTU digital flipbook: Comprehensive guidelines to produce written assignments among degree students for MPU courses / Siti Noor Ain Aziz ... [et al.] - Aziz, Siti Noor Ain; Ismail, Syaimak; Abd Rahim, Syazwani; Ali, Nurul Badriyah; Mohd Daud, Nurfarhana (2022)
Producing written papers for each course taken is one of the requirements for students at UiTM. Despite the ongoing efforts to improve academic learning, students are struggling to produce high-quality assignments. Students' inability to write quality papers can be attributed to several factors. In light of this, this research aims to offer a comprehensive guide for students on writing assignments based on the assessment rubric. This guidebook was produced to briefly explain the concepts that must be present in writing and some other components. The data collection technique uses observation, survey, and document analysis. After some research and survey, it was found that most students need proper guidelines regarding the assessment. The result showed that the digital flipbook is designed to improve the quality of producing written assignments in the MPU course. This flipbook consists of the scoring guide rubric, structure assignment, academic writing including formatting, plagiarism-checking instructions and several samples written assignments. Students can easily access the necessary information through EAC CTU552 course or freely refer to the available online resources. This innovation was chosen since there is no comprehensive guide with simple and clear instructions and explanations in the form of a digital flipbook.